Pengaruh Beban Kerja Dan Lingkungan Kerja Non Fisik Terhadap Kinerja Pegawai Pada Fakultas Hukum, Ilmu Sosial Dan Ilmu Politik Universitas Terbuka Pondok Cabe Tangerang Selatan - Nurfani; Septiowati, Rini (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2025)
The purpose of this study is to determine the effect of Workload on Employee Performance, to determine the effect of Non-Physical Work Environment on Employee Performance and to determine the Workload and Non-Physical Work Environment on Employee Performance at the Faculty of Law, Social and Political Sciences, Terbuka University Pondok Cabe, South Tangerang. The research methodology uses quantitative methods. The sample used in this study is a saturated sample with 60 respondents. The analysis method used is a simple linear regression test, multiple linear regression test, coefficient of determination, partial test (t test) and simultaneous test (F test). The results of the study indicate that: 1) Workload has a positive and significant effect on Employee Performance at the Faculty of Law, Social and Political Sciences, Terbuka University Pondok Cabe, South Tangerang, as evidenced by the calculated t value of 10.878 > t table 2.002 with a significance of 0.000 < 0.05. 2) The non-physical work environment has a positive and significant effect on employee performance at the Faculty of Law, Social, and Political Sciences, Terbuka University Pondok Cabe, South Tangerang, as evidenced by the calculated t-value of 6.722 > t-table 2.002, with a significance level of 0.000 < 0.05. 3) Workload and the non-physical work environment have a positive and significant effect on employee performance at the Faculty of Law, Social, and Political Sciences, Terbuka University Pondok Cabe, South Tangerang, as evidenced by the calculated f-value of 59.586 > F-table 3.16, with a significance level of 0.000 < 0.05.